Expressão heteróloga em Saccharomyces cerevisiae e ensaio de atividade de uma ß-1,4- endoglucanase isolada do cupim Velocitermes heteropterus (Isoptera, Termitidae) - Sabadine, Maria Augusta (2013)
The current world scenery points out that the environment changes in the Earth planet is due to the intense use of fossil fuels along decades. This panorama launched the needs for the replacement of fossil fuels to sustained renewable fuels. In this context new technologies are being developed for the production of new bioenergy sources. The lignocellulosic biomass represents an abundant renewable source of cellulose on Earth. This is certainly one of the cheapest materials and therefore has been extensively studied as source of sustainable energy for industrial purposes. Several methods for obtaining bioethanol from lignocellulosic biomass are being seeked worldwide and in that regard it is essential that the Brazil could keep its natural leadership in this field of research. In this way, the use of cellulases from eukaryotic organisms has achieved high importance in the commercially-available enzymes repertoire with purpose to degrade lignocellulosic materials in reduction sugars (glucose) for the fermentation process. The termites, eusocial insects, are potential organisms for this research investment, because they feed lignocellulosic materials and their digestory system presents the enzymes for cellulose hydrolysis generating glucose for the industrial process for production second generation ethanol.. Thus, the identification, isolation and expression of termites cellulases can be considered are a key-step to search for enzymes suitable for the use of cellulose-derived glucose in current process of ethanol production implemented in Brazil. Velocitermes heteropterus can possibly express a cellulase of interest presumably active in the fermentation tanks. In this study, we identified, sequenced and cloned one of three major enzymes of the cellulose degradation system , the endo-1,4-ßglucanase from Velocitermes heteropterus. Our results showed a high expression of its enzyme in the yeast Saccharomyces cerevisiae (FGSC9721 strain). Experiments for purification and enzymatic activity of this enzyme are in development.